(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the history of the emergence of publishing houses on the European continent and their activities are covered by the example of the Giunti publishing house located in Italy. How the publishing house became one of the leaders on the continent, the history of the Junti family, as well as some works of medieval Eastern scholars published in it are analyzed. Corrections have been made to the erroneous information in some literature